The Public-Private Partnerships and the Fiscal Soundness of Local Governments in Korea - Ho jun Lee (KDI Journal of Economic Policy, 2017)
This paper studies the risks associated with local finance in Korea by identifying the financial status of each local government, including the financial burdens of PPP projects, and examined governmental future burdens related to PPP projects. We reviewed all fiscal burdens associated with projects, such as, for BTL (Build-Transfer-Lease) types of projects, facility lease and operating expenses, and, for the BTO (Build-Transfer-Operate) types of projects, construction subsidies that are paid at the construction stage, MRG (Minimum Revenue Guarantee) payments and the government's share of payment. Furthermore, we compared the annual expenditures of local governments on PPP projects against their annual budgets and checked if the 2% ceiling rule could be applied.
Keywords: H54; H63; H72; 330; Public Private Partnership (PPP); Fiscal Burden; 2% Ceiling Rule; Fiscal Soundness; Local Government